2011
DOI: 10.4028/www.scientific.net/amm.66-68.130
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Compressive Properties of a Kind of Carbon/epoxy Composite

Abstract: In order to understand the quasi-static and dynamic compressive mechanical properties of carbon/epoxy composite laminates consisting of unidirectional carbon fiber plies and carbon fabric plies, several quasi-static and dynamic compression experiments were performed along three principal material axes. Dynamic compress experiments were conducted using the compression split Hopkinson’s pressure bar (SHPB) and MTS machine respectively. The experimental results showed that the materials had obvious strain rate ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Wang et al [15] found that the main failure modes of CF/PPS composites were delamination accompanied by shear failure under in-plane compression loads, and warp fiber bundle breakage under out-of-plane compression loads. Tian et al [16] reported that carbon/epoxy composite laminates exhibited unique characteristics in each of the three principal directions. However, there is still relatively limited knowledge regarding the quantitative characterization of dynamic mechanical properties for assessing ballistic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] found that the main failure modes of CF/PPS composites were delamination accompanied by shear failure under in-plane compression loads, and warp fiber bundle breakage under out-of-plane compression loads. Tian et al [16] reported that carbon/epoxy composite laminates exhibited unique characteristics in each of the three principal directions. However, there is still relatively limited knowledge regarding the quantitative characterization of dynamic mechanical properties for assessing ballistic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it should be noted that in the experimental results of quasistatic compression, the stress-strain curve of epoxy resin shows nonlinear characteristics at the initial stage, 19 which will lead to the initial nonlinear behavior of CFRP. 2,20 Therefore, in addition to considering the thermomechanical coupling effect of instantaneous impact temperature generation at high strain rate, the initial nonlinear effect at a low strain rate also needs to be considered in order to form a complete and accurate mechanical behavior of CFRP. Although there are other problems to consider for the CFRP laminates, such as intralaminar damage, delamination evolution, microscopic failure modes, 21,22 etc., the present paper focuses only on the macroscopic thermomechanical coupling problems related to strain rate and temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it should be noted that in the experimental results of quasistatic compression, the stress–strain curve of epoxy resin shows nonlinear characteristics at the initial stage, 19 which will lead to the initial nonlinear behavior of CFRP 2,20 . Therefore, in addition to considering the thermomechanical coupling effect of instantaneous impact temperature generation at high strain rate, the initial nonlinear effect at a low strain rate also needs to be considered in order to form a complete and accurate mechanical behavior of CFRP.…”
Section: Introductionmentioning
confidence: 99%
“…Tian studied the compression performance of carbon/epoxy composite by SHPB, and the stressstrain curve was obtained by experiment. 6 Soutis carried out the compression test of carbon fiber-epoxy cylindrical rods. 7 Their materials were T300/828, and the diameter of specimen was 4 mm.…”
Section: Introductionmentioning
confidence: 99%